Randomized Clinical Trial of Peganum Oil for Knee Osteoarthritis - Zohreh Abolhassanzadeh PharmD, PhD; Elham Aflaki MD; Gholamhossein Yousefi PharmD, PhD; Abdolali Mohagheghzadeh PharmD, PhD (SAGE Publishing, 2015)
Osteoarthritis affects about 50% of people aged older than 65 years. Pain is the most important symptom in this disease. Today public interest in the use of complementary medicine, especially traditional herbal medicines has increased. The present study was designed to investigate the efficacy of traditional preparation of Peganum harmala L oil on patients with knee osteoarthritis. The product has been analyzed and standardized by high-performance liquid chromatography. A double blind controlled randomized clinical trial consisting of 54 patients were performed. Patients rubbed the drug or control (olive oil) on the knee 4 drops 3 times a day for 4 weeks. The patients were asked to fill out the Western Ontario and McMaster Universities Arthritis Index and Visual Analogue Scale questionnaires at week 0 and 4. The adapted results from the questionnaires showed that pain and difficulty in function were significantly decreased in Peganum oil group after 4 weeks. There was no significant difference in stiffness change between 2 groups.